The Significance of IDH1 Mutations in Tumor-Associated Seizure in 60 Chinese Patients with Low-Grade Gliomas - Ruofei Liang; Yingjun Fan; Xiang Wang; Qing Mao; Yanhui Liu (The Scientific World Journal)
Background. Seizure is a common clinical presentation in patients suffering from primary brain tumors, especially from low-grade gliomas (LGGs). However, the genetic factors of tumor-associated seizure, at present, are still very poorly understood. The aim of this study was to investigate the potential correlation between tumor-associated epilepsy and IDH1 mutations in a Chinese population with LGGs. Materials and Methods. This study reviewed 60 patients with histologically confirmed low-grade gliomas, and the status of IDH1 was detected after the operation at our institution. Univariate and multivariate logistic regression analysis were used to explore the potential risk factors for tumor-related seizures. Results. IDH1 mutation was detected in 46 (76.7%) patients, among which 14 patients had no epilepsies and 32 patients had epilepsies (, chi-square test). Multivariate logistic regression analysis demonstrated that the mutation of IDH1 seems to be the strongest predictor for preoperative seizure (OR, 6.130; 95% CI, 1.523–24.669; ). Conclusions. IDH1 mutation was frequently detected in LGGs, and it may result in tumor-related seizures.